2021
DOI: 10.1002/aocs.12510
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of sinapic acid and sinapine‐derived flavor‐active compounds using a factorial‐based pressurized high‐temperature processing

Abstract: De‐oiled canola meals are sources of protein‐containing flavor‐active phenolic compounds. Conventional canola oil processing utilizes an excess amount of solvents and is associated with the release of high‐intensity bitter flavor‐active phenolic compounds, limiting the use of the canola meal. Recent advances in the extraction and isolation of the bitter favor‐active phenolic compounds from canola by‐products produce protein isolates, however, would benefit the industry by producing a side‐stream ingredient ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
(147 reference statements)
0
3
0
Order By: Relevance
“…Malik and Saini (2017) reported a 90% reduction in phenolics for sunflower protein isolated prepared by first extracting the kernels with 60% methanol followed by protein isolation. Nandasiri et al (2021) reported that 70% methanol tended to remove kaempferol derivative slightly better than 70% ethanol using accelerated solvent extractions.…”
Section: Non-volatile Organic Compoundsmentioning
confidence: 99%
“…Malik and Saini (2017) reported a 90% reduction in phenolics for sunflower protein isolated prepared by first extracting the kernels with 60% methanol followed by protein isolation. Nandasiri et al (2021) reported that 70% methanol tended to remove kaempferol derivative slightly better than 70% ethanol using accelerated solvent extractions.…”
Section: Non-volatile Organic Compoundsmentioning
confidence: 99%
“…The application of higher temperatures (>140 o C) for shorter time intervals during the process of air-frying and consistent circulation of hot air throughout the system make its ideal to preserve the nutrients and phenolic compounds without leaching out [7]. Furthermore, in both canola and mustard it was observed that certain thermo-generative phenolic compounds were also formed during the thermal process of air-frying including canolol [7,8,16,30,31]. Canolol and other thermo-generative phenolic compounds has demonstrated higher antioxidant potential in the respective studies.…”
Section: Impact Of Thermal Processing On Total Phenolic (Tpc) and Tot...mentioning
confidence: 99%
“…The formation of canolol from sinapine and sinapic acid is presented in Figure 1. Canolol is an unstable compound, and in the presence of oxygen forms derivatives such as dimers, trimers, and oligomers (Harbaum‐Piayda et al, 2010; Kraljić et al, 2015; Nandasiri, Eskin, et al, 2021; Nandasiri, Imran, et al, 2021; Nandasiri, et al 2021c). Moreover, because of its polarity, canolol can be complex with proteins and polysaccharides.…”
Section: Compositionmentioning
confidence: 99%